Educational Technology-The Futures - Mukhopadhyay, M. (Journal of Engineering Education Transformations, 1991)
I have been tossing with a variety of ideas on "Educational Technology - The future". Three ideas that gained currency over a period of time are (a) reflection on methodologies of future forecasting, like future scan, Delphi, Scenario Building and/or trend analysis, technology assessment, etc.